1995
DOI: 10.2169/internalmedicine.34.886
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumors of the Liver and Pancreas Associated with Elevated Serum Prostatic Acid Phosphatase.

Abstract: A58-year-old manwasrevealed to have multiple liver tumors with elevated prostatic acid phosphatase (PAP) during a medical examination. The tumors were ofneuroendocrine nature, but no abnormal findings were obtained in other organs in which neuroendocrine tumors develop frequently. Repeated transarterial embolization was partially effective. However, the tumors became resistant to the therapy three years later, continued growing and ruptured. Autopsy disclosed neuroendocrine tumors in the pancreas, which were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Unexpectedly, recent studies have shown strong expression of PAP by breast cancer cells (24) and elevated levels of PAP in tumors of neuroendocrine origin (25). Whether this phenomenon gives an advantage to proliferating cells or is just an aberration of cancer biology remains an open question.…”
mentioning
confidence: 99%
“…Unexpectedly, recent studies have shown strong expression of PAP by breast cancer cells (24) and elevated levels of PAP in tumors of neuroendocrine origin (25). Whether this phenomenon gives an advantage to proliferating cells or is just an aberration of cancer biology remains an open question.…”
mentioning
confidence: 99%
“…84,85 As there are few controlled studies, the potential usefulness of octreotide and interferons is currently speculative. [89][90][91] [89][90][91] …”
Section: Medical and Interventional Treatmentmentioning
confidence: 99%